THE CO-RELATION BETWEEN QWL AND DEMOGRAPHIC FACTORS OF PRIVATE UNIVERSITY EMPLOYEES IN INDIA - Ahmad, Shoeb (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this study is to evaluate the degree of QWL of University employees and, to explore the association between QWL and some demographic characteristics among them. The study adopted a case study research method. The investigation was carried out in the University, and the universe of the study comprises of employees from University. The sample was made up of both males and females, from all the race groups within the University. Primary data was used for research whereas secondary data was utilized for literature review. The study suggested statistically significant correlation between the demographic variables namely age, period of service, income and education of employees of University and QWL. Also, it concluded that employees’ gender has no specific relation regarding the degree of their QWL. The study suggests that quality of work life condition in the University is favorable to the total job environment of its employees. The paper focuses on two questions: what is the level of ‘Quality of Work Life’ of employees of the University? And is there any relationship between gender, age, work experience, income &educational qualification of the employees and their QWL. The overall findings of this study are quite encouraging and will contribute to the extant literature in a positive way. It is expected that the contribution from this study will help the top management from this organization in developing apposite policies that can augment employees’ satisfaction with their personal as well as professional lives.